2021
DOI: 10.3390/genes12121996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bacterial Community of Rumen in Dairy Cows with Laminitis

Abstract: Laminitis is the inflammation of the lamella, and it has caused great economic loss to the dairy industry and attracted wide attention around the world. In recent years, microbiota are considered to play a significant role in various diseases processes. Therefore, our study aimed to explore the characteristics of ruminal microbiota in laminitis cows. The serum of bovines with or without laminitis was collected to detect concentrations of lipopolysaccharide (LPS), lactic acid, and histamine, and ruminal fluid w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…was confirmed in a previous study, and always isolated from some human clinical subjects [60]. In addition, Candidatus Saccharimonas were found to proliferate in the intestinal lumen of parasite-infected sheep [61] and rumen of dairy cows suffering from laminitis [39]. Therefore, consistent with the changes observed in the digesta-associated microbiota, these results showed that an HP diet seemed to be able to partially alleviate the adverse effects of HG diets.…”
Section: Changes Of the Microbial Community In Jejunal Mucosa-associa...supporting
confidence: 84%
See 1 more Smart Citation
“…was confirmed in a previous study, and always isolated from some human clinical subjects [60]. In addition, Candidatus Saccharimonas were found to proliferate in the intestinal lumen of parasite-infected sheep [61] and rumen of dairy cows suffering from laminitis [39]. Therefore, consistent with the changes observed in the digesta-associated microbiota, these results showed that an HP diet seemed to be able to partially alleviate the adverse effects of HG diets.…”
Section: Changes Of the Microbial Community In Jejunal Mucosa-associa...supporting
confidence: 84%
“…Strains of Acetitomaculum were obligate anaerobe and fermented various substrates (such as glucose, fructose, and cellobiose) to acetate in the rumen of ruminants [36,37]. The evidence indicated that the ruminal Candidatus Saccharimonas was significantly and positively correlated with proportion production [38], and a significant increase in these microorganisms in the rumen of dairy cows suffering from laminitis has been reported [39]. Meanwhile, we also found a significant decrease in some beneficial microorganisms, such as Christensenellaceae R-7 group and Blautia, in the animals in the HG diets group compared to those in the CON group.…”
Section: Changes In the Microbial Structure Of Jejunal Digesta After ...mentioning
confidence: 99%
“…The former characterises the microbial community of vertebrates (i.e. 60 ), and therefore we excluded that its presence in gut microbiota of lizards was due to a conditioning by the microbiota of the moth.…”
Section: Discussionmentioning
confidence: 99%
“…SARA causes the pH of the system to decrease and subsequently activates vascular activity, increasing blood pressure in the vascular system of the hoof. Meanwhile, rumen endotoxins and histamine are released into the bloodstream, increasing vasoconstriction and dilation [ 39 ]. Subsequent vascular damage with oedema, dermal congestion and even thrombus formation eventually leads to dilation of the dermis and increasing severity of laminitis [ 40 ].…”
Section: Relationship Between Sara and Its Related Inflammatory Disea...mentioning
confidence: 99%
“…The critical link between lactic acidosis and laminitis appears to be associated with persistent hypoperfusion, which results in ischemia in the digit [ 42 ]. In addition, our recent study found that laminitis in dairy cows was not only associated with elevated levels of lactate and LPS but also closely related to the bacterial community of the rumen, characterized by elevated abundance of bacteria that enrich acid-enhancing metabolites [ 39 ].…”
Section: Relationship Between Sara and Its Related Inflammatory Disea...mentioning
confidence: 99%